ANALISIS TINGKAT KESEHATAN BANK MENGGUNAKAN METODE RGEC PADA PT. BANK SULUTGO PERIODE 2014-2016 - Yeusy Gandawari; William A. Areros; Dantje Keles (JURNAL ADMINISTRASI BISNIS, 2017)
The business activities of the bank are always faced with risks that are closely related to its function as a financial intermediation institution, required the assessment of the level of health of banks to increase public confidence against a bank research purposes of knowing the level of Bank Health on PT. Bank SulutGo reviewed aspects ofRGEC in 2014-2016. Based on reviews of existing problems, this research was conducted with the use ofex-post facto approach. The study was conducted to examine the events that have happened and then meruntut back to find out the factors that may cause the incident the results of the research and data analysis that has been done shows the risk profile (Risk Profile) SulutGo bank using two indicators of credit risk factors, namely by using the ratio of NPL and liquidity risk ratio LDR during the year 2014-2016 in a roware in healthy condition; Good Corporate Governance (GCG), Bank SulutGo in 20142015 composite gained 3 which shows quite well in the implementation of corporate governance and in 2016 rose to composite 2 which reflects that corporate governance is getting better; entabilitas (earnings) bank SulutGo by using the indicators i.e.ROA, ROE, NIM and BOPO during 2014-2016 are in a healthy condition, the value ofthe average ROA, ROE, NIM and BOPO obtained shows that the bank SulutGo has successfully run their operations effectively; The results of the assessment of capital(capital) SulutGo Bank during the year are in healthy condition is 20142016, which is above the minimum standard set by the Bank of Indonesia that is 8%. This suggests that during that period the bank SulutGo have been able to manage capital well.Â Â  Keywords: Bank, Methods Of Health Rgec